Dampak Ukuran Sensor Kamera Dijital Dalam Kemampuan Untuk Mendeteksi Pergeseran Deformasi Struktur - Tjahjadi, Martinus Edwin (AI Society & STMIK Indonesia, 2024)
Digital camera sensors such as CCD (Charge Coupled Device) or CMOS (Complementary Metal Oxide Semiconductor) are semiconductor devices for converting a captured light passing through the lens into digital photos. Their size and dimension are varyied among camera’s brands and types available on the market. This article reviews whether their size differences could affect on the camera's ability to detect the smallest possible shifts in structural deformation. Two different types of sensor sizes, namely full frame type and APSC (Advanced Photo System type C) from two different camera brands are evaluated on the sensor's ability to detect deformation. Close range photogrammetry (CRP) technique is used to observe on bridge pillar structures that were suspected of experiencing vertical movement. results show that sensor differences affect the camera's ability to distinguish smallest possible deformation. The larger the camera sensor size, the more detailed the deformation or structural shift that can be discerned.